From ‘On-stilts’ to ‘On-ground’: Spatial Form Development of Sarawak River Malay Houses inKuching, Malaysia, 1840s-1960s - Yon Syafni, Samat; Aiman, Mohd Rashid; Nurakmal Abdullah, @ Goh Tuo Ho; Atta Idrawani, Zaini; Iziq Eafifi, Ismail; Syed Ahmad Iskandar, Syed Ariffin (Faculty of Built Environment, University of Malaya., 2024)
The Malays in Sarawak have lived in riverine settlements since pre-colonial times, with the Sarawak River in Kuching housing the largest Malay population. Kampung Seberang, on the river’s north bank opposite Kuching Waterfront, holds the highest Malay concentration and historical significance, yet the architectural development of Malay houses in this area remains understudied. This paper investigates the most common house form and spatial layout of houses in Kampung Seberang, tracing its spatial form development. Using archival research, fieldwork observations and interviews, 47 samples were selected based on predetermined criteria. Samples were categorized into architectural types and mapped to uncover settlement patterns. The findings reveal four architectural styles: (1) bumbung panjang, (2) potong Limas, (3) limas Serani, and (4) hybrid limas Serani. Type 2 houses are most common near the Astana, while Type 3 houses are found further away-indicating newer settlements with differing lifestyles. The study concludes that Kampung Seberang’s architectural development is closely linked to socio-economic changes in the 1940s and infrastructure development in the 2000s, significantly altering spatial uses and house forms. As Sarawak's riverbank settlements face redevelopment, these findings can guide conservation efforts, inform preservation policies, and standardize the evaluation of architectural significance, to safeguard Sarawak’s rich architectural legacy for future generations.